2018
DOI: 10.1016/j.jml.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Adults with poor reading skills, older adults, and college students: The meanings they understand during reading using a diffusion model analysis

Abstract: When a word is read in a text, the aspects of its meanings that are encoded should be those relevant to the text and not those that are irrelevant. We tested whether older adults, college students, and adults with poor literacy skills accomplish contextually relevant encoding. Participants read short stories, which were followed by true/false test sentences. Among these were sentences that matched the relevant meaning of a word in a story and sentences that matched a different meaning. We measured the speed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 148 publications
(172 reference statements)
1
11
0
Order By: Relevance
“…It also evaluates the identification of assumptions, the derivation of implications, and the recognition of argumentative and rhetorical strategies. McKoon and Ratcliff (2018). A decisionmaking model combined with tests of particular comprehension processes can lead to further understanding of reading skills.…”
Section: Textmentioning
confidence: 99%
“…It also evaluates the identification of assumptions, the derivation of implications, and the recognition of argumentative and rhetorical strategies. McKoon and Ratcliff (2018). A decisionmaking model combined with tests of particular comprehension processes can lead to further understanding of reading skills.…”
Section: Textmentioning
confidence: 99%
“…Fixation duration times decreased with increasing predictability amongst both age groups, suggesting that context facilitates reading in both age groups to the same extent. This is further supported by research in which older adults and college students read stories followed by true or false statements that either matched or mismatched the context of the story [23]. Older adults were able to use contextually relevant information as well as younger adults to facilitate language comprehension.…”
Section: Sentence Context and Word Processing In Ageingmentioning
confidence: 72%
“…In general, studies suggest that older adults can benefit from context predicting or priming upcoming words. However, while some studies suggest that older adults can benefit from semantic context to the same extent as younger adults [10,[22][23][24] or even more than younger adults [20,21], other studies have suggested that older adults cannot use the semantic context as effectively [6][7][8].…”
Section: Matched Sentence Contexts and Ageingmentioning
confidence: 99%
“…On that assumption, as Reading is an exchange of graphemes and lexical components organized into semantic values (Núñez-Vázquez & Crismán-Pérez, 2017; Young-Suk, 2015), there are several correlative factors between reading comprehension and language awareness associated with Reading as a cognitive and visual action (McKoon & Ratcliff, 2018). This can be described by two approaches: intrinsic and an extrinsic one.…”
Section: Language Awareness Reading Comprehension and Foreign Languamentioning
confidence: 99%